2020
DOI: 10.1371/journal.pone.0235320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stand variables on stemflow and surface runoff in pine-oak forests in northern Mexico

Abstract: The flow of water in temperate forests depends on the amount of precipitation, type of soil, topographic features, and forest cover, among other factors. Unlike the first three, forest cover can be modified by silvicultural treatments, the effects of which manifest in the quality and quantity of water, as well as in the transport of sediments and soil nutrients. The objective of this study was to analyze the effect of some stand variables on surface runoff and stemflow in pine-oak forests of northern Mexico. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Overall, our study was consistent with those that have reported increases in surface runoff following forest harvest treatments [23,24]. Changes in runoff were greater following larger reductions in basal area.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, our study was consistent with those that have reported increases in surface runoff following forest harvest treatments [23,24]. Changes in runoff were greater following larger reductions in basal area.…”
Section: Plos Onesupporting
confidence: 92%
“…Contrarywise, Mediterranean forests with 18% removal did not show increase in water yield during the first and second year after cutting [31]. Cruz-Garcia, et al, found that the minimum SR values were observed in forests with a basal area higher than 20 m 2 ha -1 [23]. Rivera-Ruiz, et al, [32] in a river basin in central Mexico, found values of 0.03%, 0.09%, 2.14%, and 4.92% SR for forest plantations with pine, native grassland, grass, and soil without vegetation, respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most of the resources required for plant development are found in the soil [12,17,[22][23][24][25], and soil physical and chemical properties strongly influence species composition at the local scale [12,16,17], while influencing tree distribution even more strongly than climate in some temperate forests [9]. Therefore, climate and soil variables are together strong predictors of the occurrence of some plant species.…”
Section: Introductionmentioning
confidence: 99%